First in situ determination of the thermal performance of a U-pipe borehole heat exchanger, in Cyprus - Florides, Georgios A.; Kalogirou, Soteris A. (My University, 2008)
A ground heat exchanger can be used for the injection or extraction of thermal energy into/from the ground. The line source model is an easy method of evaluating the characteristics of the borehole and does not need expensive equipment. This method is presented and a test is performed in order to determine a borehole’s characteristics in layers consisting of clay, silt and sand at various analogies. For the borehole under test the ground thermal conductivity (λ) was found to be 1.605 W/(m K) and the effective borehole thermal resistance (Rb) to be 0.257 K/(W/m). The accuracy of the collected data could be affected mainly by two factors. The first factor is the daily flux penetration through the ground which gradually increases the temperature of the top layers and the second factor is a variation of the heating coil injection rate per active length of borehole. As it was observed this combined effect has a negligible result on the mean fluid temperature during the test hours of 280–400, when the system was operating at steady state. The steady state conditions yield values of borehole thermal resistance which deviates about 25% from the values given by the line source method. The ground thermal conductivity deviates only about 5%. This method however is not suitable for estimating the above values because of the uncertainty that exists in the estimation of the mean ground temperature, which is not constant throughout the borehole length nor is it constant at different points in a cross section of the grout. Also this method takes a lot of time until the steady state is reached.
Keywords: Borehole; Ground thermal conductivity; Line source method